2019
DOI: 10.1002/jctb.6006
|View full text |Cite
|
Sign up to set email alerts
|

Construction of immobilized CuS/TiO2 nanobelts heterojunction photocatalyst for photocatalytic degradation of enrofloxacin: synthesis, characterization, influencing factors and mechanism insight

Abstract: BACKGROUND: Numerous antibiotics are consumed and excreted to the natural environment by humans and animals, which can cause considerable water pollution. There is strong demand to find an efficient and inexpensive photocatalyst to remove antibiotics effectively from contaminated water. RESULTS: Here, CuS/TiO 2 nanobelts (NBs) heterojunction photocatalyst immobilized on a titanium foil substrate was constructed. The morphology, structure, composition, optical, and electrochemistry characteristics were explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 57 publications
(69 reference statements)
0
15
0
Order By: Relevance
“…is excited and generates the e − /h + pair, where photogenerated e − in CB of CdS migrates to CB of TiO2 and is consumed in reactions with O2 to produce O2 •-, while h + remain in the VB of CdS. Copper sulfide (CuS), which is another metal sulfide semiconductor with narrow band gap of 2.0 eV, has also been reported to be coupled with TiO2 (Type II Heterojunction) [59,60]. Jiang et al [59] reported a 85.5% degradation of enrofloxacin and 27.7% mineralization of overall organic content using immobilized CuS/TiO2 nanobelts (Table 6).…”
Section: Coupling Of Tio 2 With Metal Sulfidesmentioning
confidence: 99%
See 1 more Smart Citation
“…is excited and generates the e − /h + pair, where photogenerated e − in CB of CdS migrates to CB of TiO2 and is consumed in reactions with O2 to produce O2 •-, while h + remain in the VB of CdS. Copper sulfide (CuS), which is another metal sulfide semiconductor with narrow band gap of 2.0 eV, has also been reported to be coupled with TiO2 (Type II Heterojunction) [59,60]. Jiang et al [59] reported a 85.5% degradation of enrofloxacin and 27.7% mineralization of overall organic content using immobilized CuS/TiO2 nanobelts (Table 6).…”
Section: Coupling Of Tio 2 With Metal Sulfidesmentioning
confidence: 99%
“…Copper sulfide (CuS), which is another metal sulfide semiconductor with narrow band gap of 2.0 eV, has also been reported to be coupled with TiO 2 (Type II Heterojunction) [59,60]. Jiang et al [59] reported a 85.5% degradation of enrofloxacin and 27.7% mineralization of overall organic content using immobilized CuS/TiO 2 nanobelts (Table 6). They elucidated the mechanisms occurring in the composite upon excitation by solar irradiation.…”
Section: Coupling Of Tio 2 With Metal Sulfidesmentioning
confidence: 99%
“…Hexagonal covellite-CuS with a bandgap of ∼2 eV and a p-type-enhances absorber abilities to cover the entire solar spectrum [18,19]. Furthermore, CuS absorbs the infrared area through plasmonic absorption emanating from copper valencies due to a high concentration of charge carriers [20,26,27]. Integration of CuS with TiO 2 can enhance photon-absorption properties to visible regions, leading to better conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…99 However, the energy band alignment of TiO 2 is not suitable for efficiently producing hydrogen through photoreduction reaction. [100][101][102][103][104] On the contrary, the absorption of 2D-TMDs is weak; however, the band alignment is suitable for the redox potential of water. Therefore, the composites formed by 2D-TMDs with TiO 2 are expected to be promising catalysts for highperformance PEC-HER.…”
Section: Tmds Co-catalysts For Pec-hermentioning
confidence: 99%